Systematic theology, v. 3 - Tillich, Paul, 1886-1965 (Herts, U.K. James Nisbet, 1963)
Contents : Part 4 : Life and the spirit; Part 5 : History and the Kingdom of God. Includes bibliographical references and index.
Donated by the Adelaide Assemblies, May, 1964
Keywords: Theology, doctrinal